Characteristics of gut microbiota in Penaeus vannamei shifted with elevated salinity - Wang, Bo; Liu, Yang; Wu, Xinhua; Liu, Yunfei; Li, Ziying; Wang, Jian; Lian, Yingli; Tang, Jiayi; Yun, Biao; Tian, Xiangli (Frontiers in Microbiology, 2025)
An increasing number of studies have evaluated the effects of host, dietary, and environmental factors on the gut microbial community of Penaeus vannamei. However, the characteristics of the gut microbial community of this species in hypersaline aquaculture environments have not yet been clarified. Our findings demonstrate that salinity has a strong impact on the gut bacterial community of shrimp. The alpha diversity of the gut bacterial community of shrimp decreased with salinity. Significant differences in the composition and abundance of the core gut bacterial taxa were observed among ponds with varying salinity, and only 13 shared core operational taxonomic units (OTUs) were identified; the abundance of potential opportunistic pathogens decreased significantly in hypersaline environments. Salinity is identified as a critically important environmental factor affecting the structure of the gut bacterial community of shrimp in hypersaline environments. The structure of the gut bacterial community of shrimp was distinct at salinities of 31–39 and 47–55, and the predicted functions differed at salinities of 31–47 and 55 based on 16S rRNA gene prediction using PICRUSt2 and principal coordinate analysis. Network analysis showed that higher salinity was associated with less connectivity and cooperation among species. Neutral Community Model analysis and the normalized stochasticity ratio revealed that stochastic processes were dominant at lower salinity; however, deterministic processes became more important as salinity increased. In addition, the community-level habitat niche breadths of the gut bacterial community decreased with salinity, which further confirmed this trend. These findings provide new insights into the characteristics of the gut bacterial community of shrimp in hypersaline environments and would contribute to the improvement of farming health management of shrimp in hypersaline ponds aquaculture practices.